2020
DOI: 10.1093/ckj/sfaa220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high cut-off dialysis for acute kidney injury secondary to cast nephropathy in patients with multiple myeloma: a systematic review and meta-analysis

Abstract: Background Acute kidney injury (AKI) caused by cast nephropathy is associated with increased morbidity and mortality among patients with multiple myeloma (MM). High cut-off haemodialysis (HCO-HD) has proven to be effective in the removal of serum light chains but the effect on clinical outcomes, especially renal recovery, remains uncertain. Methods A systematic review and meta-analysis were performed examining all randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…16 A meta-analysis that consisted of these two RCTs and three retrospective cohort studies included 276 patients and found that HCO-HD was not associated with HD independence at 3, 6, and 12 months or mortality benefit. 11 The two RCTs may have been be underpowered to show a small but clinically significant benefit on the primary outcome because of the small number of patients recruited (98 patients in the MYRE study and 90 patients in the EuLITE study). They also had differing protocols in terms of pre-dialysis care, dialysis prescription, and chemotherapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 A meta-analysis that consisted of these two RCTs and three retrospective cohort studies included 276 patients and found that HCO-HD was not associated with HD independence at 3, 6, and 12 months or mortality benefit. 11 The two RCTs may have been be underpowered to show a small but clinically significant benefit on the primary outcome because of the small number of patients recruited (98 patients in the MYRE study and 90 patients in the EuLITE study). They also had differing protocols in terms of pre-dialysis care, dialysis prescription, and chemotherapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although it is effective in the removal of FLC, it also leads to the removal of essential molecules including albumin (68 kDa). [9][10][11] The introduction of medium cutoff (MCO) dialyzer allows for the elimination of FLC like the HCO dialyzer, yet has the ability to retain albumin. 12 It has also been found to be safe and well tolerated as compared to high-flux HD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high clearance properties of HCO-HD versus HF-HD for FLCs and the higher hematological response at 3 months were also confirmed in a meta-analysis incorporating the results of these two RCTs and three cohort studies ( 44 , 53 , 54 ). Nevertheless, no significant difference was found between HCO-HD and HF-HD in terms of improving renal recovery outcomes ( 58 ). In another study of 83 patients with AKI secondary to MM, in which 31 patients needed dialysis, bortezomib-based triplets were associated with a high potential for kidney response ( 59 ).…”
Section: Hco-hd Research and The Removal Of Flcsmentioning
confidence: 99%
“…A recent meta-analysis, which included data from these two randomized trials as well as from three observational studies, noted heterogeneity between study populations but found no difference in survival or renal benefits with HCO-HD versus conventional HD, though a trend toward higher dialysis independence was seen in the HCO-HD group. 24 Hemodiafiltration with ultrafiltrate regeneration offers an alternative approach to removing monoclonal FLCs and has been associated with less albumin loss than HCO-HD. 25 A small observational study 26 suggested that hemodiafiltration with ultrafiltrate regeneration may result in sustained FLC reduction with potential for renal recovery in patients with RI and MM.…”
Section: Novel Rrmm Treatments For Patients With Rimentioning
confidence: 99%